Synthesis and selective recognition property of Ni2+‐imprinted microporous polymer beads. (5th June 2013) - Jiang, Yang; Kim, Dukjoon
Abstract : Nickel ion‐imprinted polymer (IIP) was synthesized from dimethylglyoxime and 4‐vinyl pyridine monomers. These functional monomers were self assembled with the Ni 2+ template and then copolymerized with divinylbenzene and ethylene glycol dimethacrylate crosslinkers in toluene porogen via suspension polymerization. Imprinting was achieved by removing the template ion from the copolymers by extensive washing. The IIP particles produced were 300–700 µm in diameter and were spherical. The chemical and physical structures were characterized by Fourier transform infrared spectroscopy, energy dispersive X‐ray spectroscopy, and Brunauer–Emmett–Teller analysis. The adsorption capacity and kinetics, and separation selectivity were investigated using atomic adsorption spectroscopy in batch adsorption operation mode. The Ni 2+ ‐imprinted polymers showed excellent adsorption ability and selective separation property. The adsorption capacity for Ni 2+ was 320 µmol/g, and the selectivity factors ( α ) for Cu 2+, Zn 2+, Fe 2+, and Cd 2+ were 6, 11, 12, and 27, respectively. The adsorption capacity and separation selectivity were affected by the environmental pH, as the protonation easily took place in acidic condition. Copyright © 2013 John Wiley & Sons, Ltd.